Semi-analytical buckling analysis of reinforced concrete columns exposed to fire. (January 2015) - Bajc, U.; Saje, M.; Planinc, I.; Bratina, S.
Abstract: A new semi-analytical procedure is derived for the determination of buckling of the reinforced concrete column exposed to fire. The fire analysis is performed in three separate steps, of which the time development of temperatures in the fire compartment is performed first, followed by the coupled heat and moisture transfer analysis and, finally, by the mechanical analysis. A particular emphasis has been given to the critical buckling time and the remaining critical buckling load at a selected time. For this purpose, a parametric study has been performed by which the influence of different geometric parameters on the buckling load capacity of reinforced concrete columns has been assessed. The results of this study show that the load-carrying capacity of the column reduces significantly with the increasing time of fire exposure and the column slenderness. Moreover, the initial mechanical load has a small, although not negligible effect on the buckling load capacity. Abstract : Highlights: The semi-analytical model for analysis of RC column in fire is presented. The critical buckling time and the load-carrying capacity are determined. A good agreement between numerical and experimental results is found out. The initial mechanical load has a small effect on the buckling load capacity.